"It's not a seven-headed beast": abortion experience among women that received support from helplines for medication abortion in restrictive settings. Issue 10 (2nd October 2020) - Baum, Sarah E.; Ramirez, Ana Maria; Larrea, Sara; Filippa, Sofia; Egwuatu, Ijeoma; Wydrzynska, Justyna; Piasecka, Magdalena; Nmezi, Sybil; Jelinska, Kinga
Abstract: There are a growing number of abortion helplines where counselors provide person-centered medication abortion services in legally restrictive settings. Few researchers have explored the perceptions and experiences of the people who obtain support from these helplines. Between April and August 2017, we conducted 30 interviews with women who had a medication abortion with support from helpline counselors in Poland, Brazil, or Nigeria. Before seeking care with the helpline, women often heard negative stories about abortion and faced enacted stigma from the formal healthcare sector, or chose not to seek services from their doctors due to fear of stigmatizing treatment. Conversely, during their care with the helpline counselors, women received clear information in a timely manner, and were treated with kindness, compassion, respect, and without judgment. Many women gained knowledge and understanding of medication abortion, and some gained a sense of community among those who experienced abortion. Helpline models can provide high-quality, person-centered abortion care to people seeking abortions in legally restrictive contexts. Evidence from these service-delivery models could help improve service within the formal healthcare systems and expand access to high-quality, safe abortion by redefining what it means to provide care.